Development of an Enrichment Book for Writing Fable Texts Oriented to Creative Thinking Containing Values ​​of Pancasila Student Profiles for Middle School Students - Dwi Setyoningsih; Tommi Yuniawan; Rahayu Pristiwati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Current books only contain material without integrating character education. This research aims to describe the need for book development, develop a prototype enrichment book, describe expert assessments, and test the effectiveness of the book on a limited scale. This research uses Research and Development (R&D) methodology by utilizing data on the needs of students and educators. The results show that the prototype enrichment book for writing fable texts oriented towards creative thinking, incorporating the values of the Pancasila Student Profile for junior high school students, consists of (1) the book cover, (2) the introduction, (3) the main content, and (4) the conclusion. Validation tests conducted by two experts resulted in an average score of 89.95, which is categorized as good. Effectiveness testing indicates that the enrichment book is effective in writing fable texts, as evidenced by the improvement in pretest and posttest scores with a t-test result of Sig (2-tailed) 0.01 < 0.05. The benefit of this research is as a resource for deepening the skills in writing fable texts and instilling the values of the Pancasila Student Profile.